2021
DOI: 10.1007/s10508-021-02140-3
|View full text |Cite
|
Sign up to set email alerts
|

Pornography Use Profiles and the Emergence of Sexual Behaviors in Adolescence

Abstract: This research longitudinally explored adolescent pornography (porn) consumption and its association with sexual development in early and middle adolescence. A four-wave design with half-year intervals investigated pornography consumption and different (sexual) activities, such as masturbation, French kissing, petting, giving/receiving manual and oral sex, and intercourse, among 630 respondents (47.9% female, mean age 13.7 years; SD = 0.48) years at T1). A latent growth mixture analysis of pornography consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 69 publications
(101 reference statements)
0
12
0
2
Order By: Relevance
“…21 In another study, comparing high and low pornography viewing over a 4-wave longitudinal analysis, at every half-year interval, it was found that high porn using boys were substantially larger as compared to that of girls and pornography consumption was associated with the accelerated growth of sexual activities for both genders across early and middle adolescence. 22…”
Section: Consequences Of Watching Pornographymentioning
confidence: 99%
See 1 more Smart Citation
“…21 In another study, comparing high and low pornography viewing over a 4-wave longitudinal analysis, at every half-year interval, it was found that high porn using boys were substantially larger as compared to that of girls and pornography consumption was associated with the accelerated growth of sexual activities for both genders across early and middle adolescence. 22…”
Section: Consequences Of Watching Pornographymentioning
confidence: 99%
“…21 In another study, comparing high and low pornography viewing over a 4-wave longitudinal analysis, at every half-year interval, it was found that high porn using boys were substantially larger as compared to that of girls and pornography consumption was associated with the accelerated growth of sexual activities for both genders across early and middle adolescence. 22 On behavioral changes, a study by Braithwaite et al, after longitudinal assessment, showed that students who watched pornography more usually promoted more permissive scripts, were involved more in casual dating and "one-night stands," had a higher incidence of "friends with benefits" behavior, hooked up often with their sexual partners. 23 and had planned to have more sexual partners in the future.…”
Section: Consequences Of Watching Pornographymentioning
confidence: 99%
“…It is then, where a cycle of constancy - repetitive behavior for self-satisfaction through the use of pornography- based on visual and physical self-satisfaction through the use of pornography begins. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“… 16 However, currently, there is no evidence of a relationship between constant exposure to pornography and the development of maladaptive behaviors. 6 , 17 Therefore, it is not a determinant in psychosocial development as it may cause premature development of more intimate knowledge of the sexual sphere. 6 , 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation